Negative electrode for non-aqueous electrolyte secondary battery and method for producing same
The negative electrode for nonaqueous electrolyte secondary batteries, incorporating alloy-based and carbon-based active materials with curved SWCNTs, addresses the issue of capacity retention rate decline in cycling tests, enhancing battery performance and longevity.
Patent Information
- Application Number
- JP2022198432
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-12-13
AI Technical Summary
The capacity retention rate of the negative electrode for nonaqueous electrolyte secondary batteries decreases in cycling tests, as observed in existing technologies.
A negative electrode for nonaqueous electrolyte secondary batteries is developed, featuring a negative electrode active material layer composed of alloy-based and carbon-based active materials, single-walled carbon nanotubes (SWCNTs) with an average length of 1 μm or more and an average diameter of 0.05 μm or less, and a binder. The SWCNTs have a curved structure with one or more inflection points, and their content is between 0.01% and 0.2% by mass based on the active material layer.
The proposed negative electrode effectively suppresses the decrease in capacity retention rate during cycle tests, maintaining battery performance over multiple cycles.
Smart Images

Figure 0007671728000002 
Figure 0007671728000003 
Figure 0007671728000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative electrode for a non-aqueous electrolyte secondary battery, a method for producing the same, and a non-aqueous electrolyte secondary battery. [Background technology]
[0002] A negative electrode for a non-aqueous electrolyte secondary battery containing graphite and fibrous carbon is known (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-99955 Summary of the Invention [Problem to be solved by the invention]
[0004] The negative electrode for a non-aqueous electrolyte secondary battery of Patent Document 1 may have a decreased capacity retention rate in a cycle test. An object of the present disclosure is to provide a negative electrode for a non-aqueous electrolyte secondary battery (hereinafter also referred to as a negative electrode) and a non-aqueous electrolyte secondary battery, in which the decrease in the capacity retention rate in a cycle test is suppressed, and a method for manufacturing the negative electrode. [Means for solving the problem]
[0005] The present disclosure provides the following negative electrode, nonaqueous electrolyte secondary battery, and method for producing a negative electrode. [1] A negative electrode for a non-aqueous electrolyte secondary battery comprising a negative electrode active material layer, the negative electrode active material layer including a negative electrode active material, carbon nanotubes (hereinafter also referred to as CNTs), and a binder, the negative electrode active material including an alloy-based negative electrode active material and a carbon-based negative electrode active material, the CNTs including single-walled carbon nanotubes having a curved structure (hereinafter also referred to as curved SWCNTs), the curved SWCNTs having an average length of 1 μm or more and an average diameter of 0.05 μm or less, the curved SWCNTs being in contact with particles other than the particles. [2] The negative electrode for a nonaqueous electrolyte secondary battery according to [1], wherein the curved structure has one or more inflection points. [3] The negative electrode for a nonaqueous electrolyte secondary battery according to [1] or [2], wherein the content of the CNTs is 0.01% by mass or more and 0.2% by mass or less based on the negative electrode active material layer. [4] The negative electrode for a nonaqueous electrolyte secondary battery according to any one of [1] to [3], wherein a ratio of a particle size D50 of the alloy-based negative electrode active material to a particle size D50 of the carbon-based negative electrode active material is 0.40 or less. [5] The negative electrode for a nonaqueous electrolyte secondary battery according to any one of [1] to [4], wherein the CNTs further include CNTs other than the curved SWCNTs. [6] The negative electrode for a nonaqueous electrolyte secondary battery according to any one of [1] to [5], wherein the negative electrode active material has a surface, as viewed in the thickness direction, in a region having an area of 15 μm × 8 μm, a ratio of the number of SWCNTs having the curved structure to the total number of CNTs is more than 0.15 and 0.9 or less. [7] The negative electrode for a nonaqueous electrolyte secondary battery according to any one of [1] to [6], wherein the ratio of the number of SWCNTs having a length of 0.5 μm or more to the total number of the CNTs in a region of 15 μm × 8 μm on the surface when viewed in the thickness direction is 0.5 or more. [8] A method for producing a negative electrode for a non-aqueous electrolyte secondary battery according to any one of [1] to [7], comprising: a paste preparation step of preparing a paste for forming a negative electrode active material layer, the paste preparation step comprising the following steps: (a1) a step of kneading a negative electrode active material, a binder, and a dispersion medium, and (a2) a step of subsequently adding CNTs and kneading the mixture. [9] A method for producing a negative electrode for a non-aqueous electrolyte secondary battery according to any one of [1] to [8], comprising: a paste preparation step of preparing a paste for forming a negative electrode active material layer, the paste preparation step comprising the following steps: (b1) a step of kneading a negative electrode active material, a binder, and CNTs; and (b2) a step of adding a dispersion medium in an amount increased by 2% or more from an oil absorption of 70%, and kneading the mixture.
[10] A method for producing a negative electrode for a non-aqueous electrolyte secondary battery according to any one of [1] to [9], comprising: a paste preparation step of preparing a paste for forming a negative electrode active material layer, the paste preparation step comprising the following steps: (c1) mixing a negative electrode active material, a binder, a dispersion medium, and CNTs, and stirring the mixture at a peripheral speed of 230 m / min or less. Effect of the Invention
[0006] According to the present disclosure, it is possible to provide a negative electrode and a nonaqueous electrolyte secondary battery in which the decrease in the capacity retention rate in a cycle test is suppressed, and a method for producing a negative electrode. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic diagram showing an example of the configuration of the negative electrode in this embodiment. [Diagram 2] FIG. 2 is a schematic diagram illustrating the degree of curvature of a curved SWCNT. [Diagram 3] FIG. 3 is a schematic flow chart showing a method for producing a negative electrode. [Figure 4] FIG. 4 is a schematic diagram showing an example of the configuration of a battery in this embodiment. [Diagram 5] FIG. 5 is a schematic diagram showing an example of the configuration of the electrode body in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings, but the present disclosure is not limited to the following embodiments. In all of the drawings, the scale of each component is appropriately adjusted to make it easier to understand, and the scale of each component shown in the drawings does not necessarily match the scale of the actual component.
[0009] The negative electrode of the present disclosure will be described with reference to the drawings. The negative electrode 100 shown in FIG. 1 includes a current collector 10 and a negative electrode active material layer 20. The negative electrode active material layer may be provided on only one side or both sides of the current collector. The negative electrode active material layer 20 includes a negative electrode active material 21, CNTs 22, and a binder (not shown). The negative electrode active material 21 includes an alloy-based negative electrode active material 23 and a carbon-based negative electrode active material 24. The current collector 10 is a conductive sheet. The current collector 10 may include, for example, an aluminum (Al) foil, a copper (Cu) foil, or the like. The thickness of the current collector 10 may be, for example, 5 μm to 50 μm. For example, a coating layer may be formed on the surface of the current collector 10. The coating layer may include, for example, a conductive carbon material, or the like. The coating layer may have a thickness smaller than that of the negative electrode active material layer 20, for example.
[0010] The negative electrode active material 21 may include the alloy-based negative electrode active material 23 and the carbon-based negative electrode active material 24 in the form of particles. The active material particles may have any size. The particle size D50 of the particles including the alloy-based negative electrode active material 23 may be, for example, 1 μm to 10 μm, preferably 2 μm to 8 μm, and more preferably 3 μm to 6 μm. The particle size D50 of the particles including the carbon-based negative electrode active material 24 is, for example, 1 μm to 50 μm, preferably 5 μm to 40 μm, and more preferably 8 μm to 30 μm. In this specification, the particle size D50 of the active material particles represents a particle size at which the cumulative particle volume from the small particle size side in the volume-based particle size distribution is 50% of the total particle volume. The average particle size can be measured by a laser diffraction / scattering method. The ratio of the particle size D50 of the alloy-based negative electrode active material 23 to the particle size D50 of the carbon-based negative electrode active material 24 is, for example, 0.40 or less, and preferably 0.35 or less.
[0011] The alloy-based negative electrode active material 23 may include a Si-containing material. As long as the Si-containing material contains Si, it may further include additional components. The Si-containing material may include, for example, a Si / C composite material. The Si-containing material has an oxygen content of, for example, 25 wt% or less, preferably 15 wt% or less, and more preferably 7 wt% or less. When the oxygen content is within the above range, the capacity is easily improved. The Si-containing material may have voids inside. When the Si-containing material has voids inside, the porosity may be, for example, 5 vol% or more. The surface of the Si-containing material may be covered with amorphous carbon.
[0012] The carbon-based negative electrode active material 24 may include at least one selected from the group consisting of graphite, soft carbon (easily graphitizable carbon), and hard carbon (non-graphitizable carbon). The graphite may be artificial graphite. The carbon-based negative electrode active material 24 may have a BET specific surface area of, for example, 3.5 m2 as measured by a BET multipoint method. 2 / g or less, and from the viewpoint of adhesion to the Si-containing material, it is preferably 0.5 m 2 / g to 3.5m 2 / g, more preferably 1m 2 / g to 2.5m 2 / g.
[0013] The CNT22 can suppress the isolation of the negative electrode active material particles and function as a conductive material. The CNT22 includes curved SWCNTs. The curved SWCNTs can be carbon nanostructures in which a single cylindrical shape having a curved structure is composed of a single layer of carbon hexagonal mesh planes. The average length of the curved SWCNTs is 1 μm or more, preferably 1 μm to 5 μm, from the viewpoint of interparticle connectivity. The length of one curved SWCNT is, for example, 0.1 μm or more, and preferably 0.5 μm to 5 μm from the viewpoint of interparticle connectivity. The average diameter of the curved SWCNTs is 0.05 μm or less, preferably 0.015 μm or less. The length, average length, and average diameter of the curved SWCNTs are measured by the method described in the Examples section.
[0014] The curved SWCNTs are in contact with the particles of the negative electrode active material and other particles. The curved SWCNTs are more likely to follow the movement of the particles during the expansion and contraction of the negative electrode active material layer in the cycle test, so that the contact between the particles is less likely to be broken and the electron conduction path is less likely to be broken. The curved structure may have, for example, one or more inflection points, and may have two or more or three or more inflection points. The degree of curvature in the curved structure is, as shown in FIG. 2, the shortest distance W from the line segment connecting the two maximum points (or minimum points) on either side of the inflection point to the inflection point is, for example, 0.1 μm or more, preferably 0.2 μm or more. The length, average length, average diameter, inflection point, and degree of curvature of the curved SWCNTs can be adjusted by the kneading conditions in the paste preparation process. Commercially available curved SWCNTs can also be used.
[0015] The CNT22 may further include other CNTs than the curved SWCNTs. Examples of the other CNTs include single-walled carbon nanotubes and multi-walled CNTs (hereinafter also referred to as MWCNTs) that do not have a curved structure. The negative electrode active material layer has a ratio of the number of curved SWCNTs to the total number of CNTs in a region of 15 μm×8 μm on the surface when viewed from the thickness direction (hereinafter also referred to as a first number ratio) that is, for example, more than 0.15 and 0.9 or less, preferably 0.2 to 0.8. The negative electrode active material layer has a ratio of the number of SWCNTs with a length of 0.5 μm or more to the total number of CNTs in a region of 15 μm×8 μm on the surface when viewed from the thickness direction (also referred to as a second number ratio) that is, for example, 0.5 or more, preferably 0.7 or more, more preferably 0.9 or more, and even more preferably 1. The first number ratio and the second number ratio are measured by a method described in the Examples section below.
[0016] The binder includes at least one selected from the group consisting of fluororesins such as carboxymethylcellulose (CMC), polyvinylidene fluoride (PVdF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP), polytetrafluoroethylene (PTFE), polyacrylonitrile, polyimide, polyamide, acrylic resin, polyolefin, polyvinyl alcohol, polyacrylic acid (PAA), polyethylene oxide (PEO), and styrene butadiene rubber (SBR). The binder preferably includes SBR, CMC, and PAA. When the binder includes SBR, the content of SBR is preferably 0.5 to 5 mass%, more preferably 1 to 3 mass%, based on the negative electrode active material layer. When the binder includes CMC, the content of CMC is preferably 0.3 to 3 mass%, more preferably 0.5 to 1.5 mass%, based on the negative electrode active material layer. When the binder contains PAA, the content of PAA is preferably 0.5 to 5 mass %, more preferably 1 to 3 mass %, based on the negative electrode active material layer.
[0017] The thickness of the negative electrode active material layer 20 is preferably 100 to 260 μm, more preferably 120 to 200 μm. The packing density of the negative electrode active material layer 20 is preferably 1.2 to 1.7 g / cc, more preferably 1.45 to 1.65 g / cc. The negative electrode active material layer 20 may have voids, and when it has voids, the porosity is preferably 20 to 35%.
[0018] As shown in FIG. 3, the method for producing the negative electrode 100 may include a negative electrode active material layer forming paste (hereinafter also referred to as paste) preparation step (A1), a coating step (B1), a drying step (C1), and a compression step (D1). In the paste preparation step, the negative electrode active material, the CNTs, the binder, and an arbitrary amount of the dispersion medium may be mixed. The paste may have an arbitrary solid content concentration (mass fraction of solid content). The paste may have a solid content concentration of, for example, 40% to 80%. Any stirring device, mixing device, or dispersing device may be used for mixing. The negative electrode 100 may be cut to a predetermined planar size according to the specifications of the battery.
[0019] The paste preparation step may include (a1) a step of kneading a negative electrode active material, a binder, and a dispersion medium, and (a2) a step of subsequently adding CNTs and kneading them. By including (a1) and (a2), it is possible to facilitate connection between active material particles.
[0020] The paste preparation step may include (b1) a step of kneading the negative electrode active material, the binder, and the CNTs, and (b2) a step of adding and kneading a dispersion medium in an amount 2% or more greater than the oil absorption of 70%. The oil absorption of 70% refers to the amount of water added (moisture content) at which the torque measured when mixing is performed while adding water to the active material of the intended composition amount is 70% of the maximum torque. The moisture content A0 (%) and solid content B0 (%) when the dispersion medium is added in an amount 2% or more greater than the oil absorption of 70%, and the moisture content A1 (mL) per 100 g of active material at the oil absorption of 70% satisfy the relationship of the formula: B0 = 100 - A0 = [100 / (100 + A1) × 100] - 2 (%). By including (b1) and (b2), it is possible to reduce the shear during kneading and reduce the dispersion energy, thereby preventing the CNTs from being cut and shortened in length, and increasing the number of curved CNTs.
[0021] The paste preparation step may include (c1) a step of mixing the negative electrode active material, the binder, the dispersion medium, and the CNTs, and stirring the mixture at a peripheral speed of 230 m / min or less. By including (c1), the CNTs are less likely to be arranged on a single large particle of the negative electrode active material in the fluid during stirring, making it easier to connect the negative electrode active materials together.
[0022] The battery in this embodiment is preferably a prismatic battery. The battery 200 shown in FIG. 4 includes an exterior body 90. The exterior body 90 houses the electrode body 50 and an electrolyte (not shown). The electrode body 50 is connected to a positive electrode terminal 91 by a positive electrode current collecting member 81. The electrode body 50 is connected to a negative electrode terminal 92 by a negative electrode current collecting member 82. The electrode body 50 may be either a wound type or a laminated type. The electrode body 50 is preferably flat. The electrode body 50 includes a negative electrode 100. A resin sheet (electrode body holder) may be disposed between the electrode body 50 and the exterior body 90.
[0023] The electrode body shown in FIG. 5 may be either a wound electrode body or a laminated electrode body. A flat electrode body is preferable. This is a schematic diagram showing an example of an electrode body in this embodiment. The electrode body 50 is of a wound type. The electrode body 50 includes a positive electrode 20, a separator 70, and a negative electrode 100. That is, the battery 200 includes the negative electrode 100. The positive electrode 60 includes a positive electrode active material layer 62 and a positive electrode current collector 61. The negative electrode 100 includes a negative electrode active material layer 20 and a current collector (negative electrode current collector) 10. EXAMPLES
[0024] The present disclosure will be described in more detail below with reference to examples. In the examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified. <Implementation distance 1> [Preparation of negative electrode plate]: Negative electrode active material [graphite particles (D50 = 17 μm, BET = 2.2 m 2 / g), Si-containing particles (SiC) (D50 = 6.5 μm)], conductive material [fibrous carbon (single-walled carbon nanotubes, CNTs consisting of one layer)], binder (CMC, PAA, SBR), and water as a solvent were mixed using a stirring granulator to prepare a paste for forming a negative electrode active material layer. The paste for forming a negative electrode active material layer was prepared so that the mass ratio of graphite particles / SiC / SWCNT / CMC / PAA / SBR was 94 / 6 / 0.05 / 1 / 1 / 1 (mass%). In the paste preparation process, mixing and kneading were performed in the following manner. (1) Graphite, SiC, CMC, and PAA were dry mixed to prepare a first mixture. (2) Water was added to the first mixture, and the mixture was kneaded at a rotation speed of 50 rpm for 90 minutes to obtain a second mixture (solid content rate 66.5%). (3) SWCNT (a water-soluble paste with a solid content of 1%) was added to the second mixture, which was then kneaded at a rotation speed of 50 rpm for 15 minutes to obtain a third mixture. (4) Water was added to the third mixture, which was then kneaded at a rotation speed of 30 rpm for 30 minutes to obtain a fourth mixture. (5) SBR and a dispersion solvent were added to the fourth mixture to dilute it, and the mixture was mixed at a rotation speed of 30 rpm for 30 minutes to produce a paste for forming a negative electrode active material layer. A PRIMIX Hivismix 2P-1 mixer was used as the mixer. The peripheral speed during mixing in each step was 230 m / min or less.
[0025] The prepared paste for forming the negative electrode active material layer was applied onto a 10 μm Cu foil, dried, pressed to a specified thickness, and processed to a specified dimension to obtain a negative electrode plate. The coating weight on both sides was 215 μm. 2 The packing density was 1.60 g / cc. The packing density was calculated by the following formula: Z=X÷Y [Z: packing density (g / cc), X: coating weight of the active material layer (m 2 / g), Y: thickness of the active material layer (μm).
[0026] [Preparation of positive electrode plate]: A paste for forming a positive electrode active material layer was prepared by kneading a positive electrode active material [lithium nickel cobalt manganese composite oxide (NCM)], a conductive material [acetylene black (AB)], a binder (PVDF), and NMP as a solvent. The paste for forming a positive electrode active material layer was prepared so that the mass ratio of the positive electrode active material / conductive material / binder was 100 / 1 / 1. The prepared paste for forming a positive electrode active material layer was applied onto a 15 μm Al foil, dried, pressed to a specified thickness, and processed to a specified dimension to obtain a positive electrode plate.
[0027] [Preparation of test battery]: Leads were attached to the prepared negative and positive electrode plates, and the electrode plates were laminated with a separator between them to prepare an electrode body. The prepared electrode body was inserted into an exterior body made of an aluminum laminate sheet, a non-aqueous electrolyte was injected, and the opening of the exterior body was sealed to prepare a test battery (laminate cell). The non-aqueous electrolyte used was 1M LiPF6 as the Li salt, and a solvent of EC / EMC / DMC=20 / 40 / 40 (volume %) was used.
[0028] [Evaluation of the state of CNTs]: A 15 μm × 8 μm area on the surface of the negative electrode plate was observed using a SEM (Hitachi High-Tech Corporation) at an accelerating voltage of 1 kV, and the number of CNTs, the number of curved SWCNTs, and the number of SWCNTs with a length of 0.5 μm or more were counted from the image to determine the first and second number ratio. The average diameter and average length of the curved SWCNTs were also determined. The length of the curved SWCNTs was measured as the distance from one end to the other end. The results are shown in Table 1.
[0029] [Cycle retention rate]: In a 25°C environment, CC charging (0.05C_4.2V) was performed, followed by CC discharging (0.05C_2.5V cut), which constituted one cycle. (1cyc discharge capacity) / (1cyc charge capacity) was calculated as the initial efficiency. In a 25°C environment, CCCV charging (0.2C_4.2V_0.1C cut) was performed, followed by CC discharging (0.33C_2.5V cut), which constituted one cycle. Cycle testing was carried out until 100 cycles were reached. (100cyc discharge capacity) / (1cyc discharge capacity) was calculated as the cycle retention rate. The results are shown in Table 1.
[0030] <Example 2> A test battery was prepared in the same manner as in Example 1, except that the procedure in the paste preparation step in Example 1 was changed to the following procedure. (1) Graphite particles, SiC, CMC, and PAA were dry mixed to prepare a first mixture. (2) SWCNT (a water-soluble paste with a solid content of 1%) and water were added to the first mixture, and the mixture was kneaded at a rotation speed of 50 rpm for 90 minutes to obtain a second mixture (solid content of 64.5%). (3) Water was added to the second mixture, and the mixture was kneaded at a rotation speed of 30 rpm for 30 minutes to obtain a third mixture. (4) SBR and water were added to the third mixture, which was diluted and mixed at a rotation speed of 30 rpm for 30 minutes to prepare a paste for forming a negative electrode active material layer. In each procedure, water was added so that the moisture content was 2% higher than the oil absorption of 70%. In addition, the peripheral speed during stirring in each procedure was 230 m / min or less. The results are shown in Table 1.
[0031] <Comparative Example 1> A test battery was fabricated in the same manner as in Example 2, except that water was added so that the moisture content during kneading was 70% of the oil absorption. The results are shown in Table 1. <Comparative Example 2> A test battery was prepared in the same manner as in Example 2, except that in step (4), when SBR was added, a disk-shaped rotor was used to stir the mixture for 30 minutes at a peripheral speed of 235 m / min (disk with a diameter of 30 mm at 2500 rpm). The results are shown in Table 1. <Comparative Example 3> Test batteries were produced in the same manner as in Example 2, except that the CNTs in Example 2 were changed to those shown in Table 1. The results are shown in Table 1. <Comparative Example 4> Test batteries were produced in the same manner as in Example 2, except that the CNTs in Example 2 were changed to those shown in Table 1. The results are shown in Table 1.
[0032] [Table 1] [Explanation of symbols]
[0033] 10 current collector, 20 negative electrode active material layer, 21 active material particles, 22 CNT, 23 alloy-based negative electrode active material, 24 carbon-based negative electrode active material, 50 electrode body, 60 positive electrode, 61 positive electrode current collector, 62 positive electrode active material layer, 70 separator, 81 positive electrode current collector, 82 negative electrode current collector, 90 exterior body, 91 positive electrode terminal, 92 negative electrode terminal, 100 negative electrode, 200 battery.
Claims
1. A negative electrode for a non-aqueous electrolyte secondary battery comprising a negative electrode active material layer, The negative electrode active material layer includes a negative electrode active material, carbon nanotubes, and a binder, The negative electrode active material includes an alloy-based negative electrode active material and a carbon-based negative electrode active material, The carbon nanotubes include single-walled carbon nanotubes having a curved structure; The curved single-walled carbon nanotubes have an average length of 1 μm or more and an average diameter of 0.05 μm or less; The single-walled carbon nanotube having the curved structure is in contact with a particle and another particle different from the particle, the negative electrode active material layer has a surface when viewed in a thickness direction, in which a ratio of the number of single-walled carbon nanotubes having the curved structure to the total number of the carbon nanotubes in a region of 15 μm × 8 μm is 0.15 to 0.
25.
2. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 , wherein the curved structure has one or more inflection points.
3. 2 . The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 , wherein the content of the carbon nanotubes is from 0.01% by mass to 0.2% by mass based on the negative electrode active material layer.
4. 2. The negative electrode for a non-aqueous electrolyte secondary battery in accordance with claim 1, wherein a ratio of a particle size D50 of said alloy-based negative electrode active material to a particle size D50 of said carbon-based negative electrode active material is 0.40 or less.
5. 2 . The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 , wherein the carbon nanotubes further include other carbon nanotubes than the single-walled carbon nanotubes having the curved structure.
6. 2. The negative electrode for a nonaqueous electrolyte secondary battery according to claim 1, wherein the negative electrode active material layer has a surface, as viewed in a thickness direction, in a region of 15 μm×8 μm, in which a ratio of the number of the single-walled carbon nanotubes having a length of 0.5 μm or more to the total number of the carbon nanotubes is 0.5 or more.
7. A method for producing a negative electrode for a non-aqueous electrolyte secondary battery, comprising: a paste preparation step of preparing a paste for forming a negative electrode active material layer, the paste preparation step comprising the following steps: (a1) kneading a negative electrode active material, a binder, and a dispersion medium; and (a2) adding and kneading carbon nanotubes; Including, The negative electrode for a non-aqueous electrolyte secondary battery includes a negative electrode active material layer, the negative electrode active material layer includes the negative electrode active material, the carbon nanotubes, and the binder, The negative electrode active material includes an alloy-based negative electrode active material and a carbon-based negative electrode active material, The carbon nanotubes include single-walled carbon nanotubes having a curved structure; The curved single-walled carbon nanotubes have an average length of 1 μm or more and an average diameter of 0.05 μm or less; The method for producing a negative electrode for a non-aqueous electrolyte secondary battery, wherein the single-walled carbon nanotube having a curved structure is in contact with a particle and another particle different from the particle.
8. A method for producing a negative electrode for a non-aqueous electrolyte secondary battery, comprising: a paste preparation step of preparing a paste for forming a negative electrode active material layer, the paste preparation step comprising the following steps: (b1) kneading a negative electrode active material, a binder, and carbon nanotubes; and (b2) A step of adding a dispersion medium in an amount increased by 2% or more from an oil absorption of 70% and kneading the mixture. Including, The negative electrode for a non-aqueous electrolyte secondary battery includes a negative electrode active material layer, the negative electrode active material layer includes the negative electrode active material, the carbon nanotubes, and the binder, The negative electrode active material includes an alloy-based negative electrode active material and a carbon-based negative electrode active material, The carbon nanotubes include single-walled carbon nanotubes having a curved structure; The curved single-walled carbon nanotubes have an average length of 1 μm or more and an average diameter of 0.05 μm or less; The method for producing a negative electrode for a non-aqueous electrolyte secondary battery, wherein the single-walled carbon nanotube having a curved structure is in contact with a particle and another particle different from the particle.
9. 2. The method for producing a negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, further comprising a paste preparation step of preparing a paste for forming a negative electrode active material layer, the paste preparation step comprising the following steps: (c1) A step of mixing a negative electrode active material, a binder, a dispersion medium, and carbon nanotubes and stirring the mixture at a peripheral speed of 230 m / min or less. The method for producing a negative electrode for a non-aqueous electrolyte secondary battery includes the steps of:
Citation Information
Patent Citations
Large-capacity electrode
JP2019033094A
Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
JP2021099955A
Secondary battery negative electrode and secondary battery
WO2021085255A1
Secondary battery negative electrode and secondary battery
WO2022070904A1